The Influence of Multimedia with Autistic Learners from the Teachers Perception - Omar, Sarah Bakr; Choo, Koo Ah; Bidin, Azman (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The purpose of the study is to explore the perspective of teachers on the use of tablet-based applications with young autistic children through a qualitative case study approach. Eight schoolteachers were interviewed for the study. This paper reports the findings of teachers’ perceptions towards the Autism Aid application with their learners, which has been designed based on their cognitive ability and school curriculum, e.g., self-management skills. The findings showed that generalization based on the design of tablet applications used could be problematic due to the limited number of participants, as well as the potential impact of teaching philosophies and previous experiences. Second, the results have shown that motivation, the human-model, and the use of technology in the classroom affected children’s learning outcomes.